Some explanations of crime among four ethnic groups in the Netherlands - Junger, Marianne (Journal of quantitative criminology, 1992)
Since 1950 there has been large-scale immigration to Western Europe, mainly from Muslim countries. This paper focuses on the degree of involvement in crime of ethnic minority boys as compared to indigenous boys and on the possible causes of these crime involvements. A random sample from three ethnic minority boys (Moroccans, Turks, Surinamese) was taken. A control group consisted of indigenous boys with a comparable socioeconomic background as the minority respondents. Data were gathered about self-report and recorded delinquency, family and school life, leisure time, traditionalism, migration problems, and socioeconomic status. It appears that the arrest rates among the minority youths are substantially higher than among the comparable Dutch boys. A number of explanations are considered: strain, lack of social control, cultural dissonance, and migration problems. Results show that only social control factors explain criminality within the groups, indicating that the causes of criminality among ethnic minority boys may essentially be the same as those among the indigenous boys.